2019
DOI: 10.3390/ijerph16081450
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting HIV Testing among Youth in Kenya

Abstract: With the high prevalence of HIV among youth in sub-Saharan Africa, it is vital to better understand factors affecting HIV testing among this population; this is the first step in the HIV treatment cascade. The purpose of this study was to examine factors related to behavioral intentions regarding HIV testing using existing pre-test data from the HIV SEERs (Stigma-reduction via Education, Empowerment, and Research) Project, a community-based participatory research program targeting 13–24-year-olds in Kenya. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
38
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 48 publications
8
38
1
Order By: Relevance
“…The odds of getting HIV tests for Ethiopian youths who had moderate and comprehensive HIV knowledge were nearly 1.78 times higher compared to their peers who had low HIV knowledge. This finding is consistent with the results from the study done using data from four Sub Saharan countries: Burkina Faso, Senegal, South Africa, Southeast Asia, and Kenya, where youths who had higher knowledge of HIV opted in HIV test uptake [ 27 , 29 , 32 36 ]. This might be due to the reason that people with better HIV knowledge have less misconception on the disease and less stigmatized attitude towards PLWH and have higher odds of being tested for HIV.…”
Section: Discussionsupporting
confidence: 90%
“…The odds of getting HIV tests for Ethiopian youths who had moderate and comprehensive HIV knowledge were nearly 1.78 times higher compared to their peers who had low HIV knowledge. This finding is consistent with the results from the study done using data from four Sub Saharan countries: Burkina Faso, Senegal, South Africa, Southeast Asia, and Kenya, where youths who had higher knowledge of HIV opted in HIV test uptake [ 27 , 29 , 32 36 ]. This might be due to the reason that people with better HIV knowledge have less misconception on the disease and less stigmatized attitude towards PLWH and have higher odds of being tested for HIV.…”
Section: Discussionsupporting
confidence: 90%
“…After the experience of repeated HIV tests during the vaccine trial, the frequency of testing was fueled by distrust from the sexual partners, the need to know individual HIV status, availability of HIV testing equipment, and the training seminars that were provided during the trial. Similar motivators have been reported in other countries [ 51 , 52 , 53 ]. A systematic review revealed that perceived testing benefits, knowledge of testing sites, and knowing someone with HIV is the motivator for HIV testing [ 54 ].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, Nyblade et al [41] reported that female sex workers who anticipated stigma from their healthcare provider were more likely to avoid HIV testing. Similar concerns were expressed among university students, adolescents, and young adults [44][45][46]. Romo et al found a similar effect among long distance truck drivers, where anticipated stigma was associated with lowrates of HIV testing [42].…”
Section: Kenyamentioning
confidence: 74%